Vulnerabilities and academic outcomes among students in Puerto Rico - Sánchez-Cardona, Israel (Preventing school failure : alternative education for children and youth, 2022)
Violence and health inequalities impact the academic outcomes of students, especially among minority groups. This study examines the differences in grade retention and dropout intentions with respect to exposure to violence and to mental health (anxiety, depression, and trauma) among youth living in Puerto Rico. Data from 566 students of fifth to twelfth grade in Puerto Rico were collected as part of a school-based service program. A two-way ANOVA showed no significant differences in exposure to violence and mental health among students with and without a history of grade retention. However, students who reported dropout intentions showed higher exposure to violence and mental health issues. These results highlight the value of assessing mental health and contextual indicators in designing interventions to prevent adverse academic outcomes in vulnerable populations